Ethnomycological Aspects of Traditional Usage and Indigenous Knowledge about the Arid-Semi Arid Truffles Consumed by the Residents of the Eastern Anatolia Region of Turkey - Akyuz, Mehmet; Akyuz, Hayriye Esra; Kirbag, Sevda (Gazi Univ, 2017)
This research consists of a cross-sectional survey studying the local knowledge about arid-semi arid truffles, their use and their ethnomycological aspects, in the hope of discussing the importance of truffles in socioeconomic life, for the local ecology and in folk traditions. 230 truffle gatherers from Eastern Turkey were interviewed. Truffles usually appear from early March to late April (68.3%), seen at barren areas that are not plowed (95.2%), and grow in sandy soils (97.8%). Truffle gatherers look for truffle types at areas where the soil bulges and cracks (97.0%), or where kumi plant grows (95.2%), and they find these using their personal experience (94.8%). Observed species included red, reddish brown, brown (100%), yellowish white (60.4%), and rarely black (30.0%) morphological types. The locals have expressed that they collect about 2 kg or less truffles per day (68.7%), and the financial profit is high (68.3%). They acquired information from their families and elders (92.6%) about mushrooms, and they gather truffles for nutrition (97.8%), for their high nutritious value (67.8%), as they are a natural food source (94.3%), and because of the feeling of satiety they provide (95.7%). Rain (97.8%), soil type (62.2%) and also host plant (Helianthemum spp.) affect the growth of the mushroom. Truffles are usually fried with eggs when cooking (84.8%), preserved in refrigerators (93.0%), and the quality of edibility is high (83.9%). T. boudieri is preferred for commercial use, whereas other types (P. lefebvrei, T. olbiensis and P. juniperi) are mostly used for daily consumption because they do not provide financial profit.
Keywords: Ethnomycological aspect; Arid-semi arid truffle; Terfezia; Picoa; Helianthemum spp.; Indigenous knowledge; Traditional usage of truffle